Nurses' view of nursing workers in functional readaptation: Subsidies for management (Research, Society and Development, 2024)
Objective: To know the perceptions of nurses about the functional readaptation of workers in a university hospital. Methodology: This is a qualitative and descriptive study, in which 19 nurses linked to the Unified Legal Regime were interviewed. Data collection took place between May and July 2016, through semi-structured interviews. The data were analyzed and interpreted according to the thematic content analysis of Minayo's operative proposal. Results: The information converged into four categories: nurses' conception of the readapted worker; ease and difficulties in returning to work; reception of the worker and the need for a formal process in the institution. Conclusion: The functional readaptation of nursing workers still represents a challenge in health services to be overcome, since it is a very complex process.